INVESTIGATION ON THE MORPHOLOGY AND PROPERTIES OF AGGREGATE STRUCTURES OF NATURAL PHOSPHOLIPIDS IN AQUEOUS SYSTEM USING CRYO-TEM - Dwi Hudiyanti; Tri Joko Raharjo; Narsito Narsito; Sri Noegrohati (Universitas Gadjah Mada, 2012)
Cryogenic transmission electron microscopy (Cryo-TEM) was used to investigate the aggregates morphology and properties of candle tree (Aleurites moluccana) endosperm, sesame (Sesamum indicum L. syn.) seeds, and coconut (Cocos nucifera) endosperm phospholipids in dilute aqueous system. The micrographs showed that candle tree phospholipids formed planar bilayer and cluster of vesicles with lipid droplets, while coconut and sesame phospholipids formed well-defined unilamellar vesicles. The vesicles size could be as small as 50 nm in diameter. Coconut phospholipids also showed a good bending ability. Formation of clusters of vesicles was also found in coconut phospholipids dispersion, but this cluster was easily broken by extrusion through a small pore membrane.